Probiotics Intervention for Mitigation of Uterine Infection in Dairy Animals -An Update - Suthar , Vishal; Dhami , A. J.; Gohil , Purva; Joshi , Madhavi; Patil , D. B.; Joshi , C. G. (Animal Reproduction Update, 2022)
Probiotic bacteria are an important subject to explore when it comes to inhibiting infectious bacteria, also commercially available for its usage in a variety of sectors including animals and humans. Postpartum uterine infections including metritis and endometritis are common in buffaloes and cow a major problem dairy industry, as it is associated with reduced fertility and decreased milk yield. To address this issue, the present review discusses the role of probiotics in the treatment of infectious uterus and its implications in the reproductive efficiency of dairy animals. Probiotic administration in the host has proven to improve health status by competing for the nutrient utilization of infectious microbes. The antibiotic activity of probiotic bacteria is also known to reduce stress on the host. Application of the probiotic strains has been proposed as an alternative to prevent uterine infection and inflammation. Hence, this review article summarizes the effects of probiotics on metritis and endometritis in bovines. And the current studies on probiotics with their effects on the uterus include their immunomodulatory effects on the animal host.
Keywords: dairy; probiotic bacteria; strains; cattle; animal